BULLOUS PEMPHIGOID ASSOCIATED WITH SITAGLIPTIN USE: A CASE REPORT - Dela Cruz, Ma. Guia Estrella; Joven, Mark Henry; Mendoza, Clarisse; Vista, Emmerson Gale (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION DPP-IV inhibitors are considered one of the safest anti-diabetes drugs given its low hypoglycemic risk and neutral effects on weight. Recently, cases of bullous pemphigoid have been reported on patients with type 2 diabetes treated with DPP-IV inhibitors. CASE A 70-year-old Filipino male of Chinese descent presented with pruritic eczematous papular rash on both shins. Lesions progressed to blisters in the trunk and extremities. Medical history was significant for T2DM and hypertension. He was on sitagliptin 50 mg daily (started a month prior) and losartan 50 mg daily. CONCLUSION We present a patient with T2DM on sitagliptin who presented with bullous pemphigoid. Physicians should be aware of this association since early detection may circumvent its progression and avert complications.